Predictors of Response to Autologous Dendritic Cell Therapy in Glioblastoma Multiforme - Jan, Chia-Ing; Tsai, Wan-Chen; Harn, Horng-Jyh; Shyu, Woei-Cherng; Liu, Ming-Chao; Lu, Hsin-Man; Chiu, Shao-Chih; Cho, Der-Yang (Frontiers in Immunology, 2018)
BACKGROUND Glioblastoma (GBM) is the most common and lethal primary malignant glioma in adults. Dendritic cell (DC) vaccines have demonstrated promising results in GBM clinical trials. However, some patients do not respond well to DC therapy, with survival rates similar to those of conventional therapy. We retrospectively analyzed clinical and laboratory data to evaluate the factors affecting vaccine treatment. METHODS Forty-seven patients with de novo GBM were enrolled at China Medical University Hospital between 2005 and 2010 and divided into two subgroups. One subgroup of 27 patients received post-surgical adjuvant immunotherapy with autologous dendritic cell/tumor antigen vaccine (ADCTA) in conjunction with conventional treatment of concomitant chemoradiotherapy (CCRT) with temozolomide. The other 20 patients received only post-surgical conventional treatment without immunotherapy. Immunohistochemistry for CD45, CD4, CD8, programed death ligand 1 (PD-L1) and programed death 1 (PD-1) was performed on sections of surgical tumor specimens and peripheral blood mononuclear cells (PBMCs). Pearson’s correlation, Cox proportional hazard model, and Kaplan-Meier analyses were performed to examine the correlations between the prognostic factors and survival rates. RESULTS Younger age (<57 years), gross total resection, and CCRT and PD-1+ lymphocyte counts were significant prognostic factors of overall survival (OS) and progression-free survival (PFS) in the ADCTA group. Sex, CD45+ lymphocyte count, CD4+ or CD8+ lymphocyte count, tumor PD-L1 expression, isocitrate dehydrogenase 1 (IDH1) mutation, and O6 methylguanine-DNA methyltransferase (MGMT) promoter methylation status were not significant factors in both groups. In the ADCTA group, patients with tumor infiltrating lymphocytes (TILs) with a lower PD-1+/CD8+ ratio (≦0.21) had longer OS and PFS (median OS 60.97 months, P<0.001 and PFS 11.2 months, P<0.008) compared to those with higher PD-1+/CD8+ ratio (>0.21) (median OS 20.07 months, P<0.001 and PFS 4.43 months, P<0.008). Similar results were observed in patients’ PBMCs; lymphocyte counts with lower PD-1+/CD8+ ratio (≦0.197) had longer OS and PFS. There was a significant correlation of PD-1+/CD8+ ratio between TILs and PBMCs (Pearson’s correlation R2 = 0.6002, P<0.001). In contrast, CD4-, CD8-, but PD-1+, CD45+ tumor infiltrating lymphocytes have no impact on OS and PFS (P = 0.073 and P = 0.249; respectively). CONCLUSIONS For patients receiving DC vaccine